Alternative Synthesis of α-l-Threofuranosyl Guanosine 3′-triphosphate - Sarma, Daisy; Majumdar, Biju; Chaput, John C. (Synlett, 2023)
Artificial genetic polymers (XNAs) have attracted considerable attention due to their unique physicochemical properties that include enhanced chemical and biological stability. Unfortunately, some of the most interesting XNAs are constructed from monomers that are not readily available and must be prepared by chemical synthesis. The need to generate building-block materials for these systems warrants careful optimization, as syntheses of XNA monomers can easily exceed ten chemical steps. Here, we evaluate the synthesis of α-l-threofuranosyl guanosine 3′-triphosphate (tGTP), a key substrate in the enzymatic synthesis of α-l-threofuranosyl nucleic acids. Previously, tGTP was prepared by a Vorbrüggen glycosylation reaction from N-acetyl-O-(diphenylcarbamoyl)guanine and a suitably protected threose sugar. However, the preparation of the protected nucleobase was a laborious process that merited further evaluation. We now describe an alternative approach that is easier to perform and does not compromise the overall yield or regioselectivity.
Keywords: threose nucleic acids; artificial genetic polymers; medicinal chemistry; threofuranosyl guanine triphosphate; phosphorylation; glycosylation